Primer registro del género Anochetus Mayr 1861 (Hymenoptera: Formicidae) para el estado de Jalisco, México - Vásquez-Bolaños, Miguel; Meza-López, Abraham (Instituto de Ecología, A.C., 2011)
The genus Anochetus Mayr is recorded by first time from Jalisco State, and it was known just in the middle and southeastern states in México. It was collected at 9 km to South to the urban zone in Puerto Vallarta. The specimen revised belongs to species A. mayri Emery. The distribution of the genus and the species is increased to the occidental area in the county.